Melville D. Landon papers - Landon, Melville D. (Melville De Lancey), 1839-1910.
Quotation (1889) and ticket (undated) signed Melville D. Landon and Eli Perkins.
Humorist who used the pseudonym Eli Perkins.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: American wit and humor; Humorists